Early Diagnosis of Spastic Cerebral Palsy in Infants with Periventricular White Matter Injury Using Diffusion Tensor Imaging - Jiang, H.; Li, X.; Jin, C.; Wang, M.; Liu, C.; Chan, K.C.; Yang, J. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Periventricular white matter injury is the common cause of spastic cerebral palsy. However, the early diagnosis of spastic cerebral palsy still remains a challenge. Our aim was to investigate whether infants with periventricular white matter injury with bilateral spastic cerebral palsy have unique lesions different from those in infants without cerebral palsy and to evaluate the efficiency of DTI in the early diagnosis of spastic cerebral palsy.MATERIALS AND METHODS: Infants with periventricular white matter injury and controls underwent MR imaging at 6–18 months of age. Fractional anisotropy was calculated from DTI. Cerebral palsy was diagnosed by 24–30 months of age. Subjects were divided into 3 groups: infants with periventricular white matter injury with bilateral spastic cerebral palsy, infants with periventricular white matter injury without cerebral palsy, and controls. Tract-Based Spatial Statistics and Automated Fiber Quantification were used to investigate intergroup differences. Receiver operating characteristic curves were used to assess the diagnostic accuracy of spastic cerebral palsy. Correlations between motor function scores and fractional anisotropy were evaluated along white matter tracts.RESULTS: There were 20, 19, and 33 subjects in periventricular white matter injury with spastic cerebral palsy, periventricular white matter injury without cerebral palsy, and control groups, respectively. Decreased fractional anisotropy in the corticospinal tract was only observed in infants with periventricular white matter injury with spastic cerebral palsy, whereas decreased fractional anisotropy in the posterior thalamic radiation and genu and splenium of the corpus callosum was seen in both periventricular white matter injury subgroups. Fractional anisotropy in the corticospinal tract at the internal capsule level was effective in differentiating infants with periventricular white matter injury with spastic cerebral palsy from those without cerebral palsy by a threshold of 0.53, and it had strong correlations with motor function scores.CONCLUSIONS: Corticospinal tract lesions play a crucial role in motor impairment related to spastic cerebral palsy in infants with periventricular white matter injury. Fractional anisotropy in the corticospinal tract at the internal capsule level could aid in the early diagnosis of spastic cerebral palsy with high diagnostic accuracy.CPcerebral palsyCSTcorticospinal tractCST-CPCST at the cerebral peduncle levelCST-CRCST at the corona radiata levelCST-ICCST at the internal capsule levelFAfractional anisotropyGCCgenu of the corpus callosumGMFCSGross Motor Function Classification SystemPTRposterior thalamic radiationPWMIperiventricular white matter injurySCCsplenium of the corpus callosumSCPspastic cerebral palsy